In silico exploration of small-molecule α-helix mimetics as inhibitors of SARS-COV-2 attachment to ACE2. Issue 4 (4th March 2022) - Hakmi, Mohammed; Bouricha, E L Mehdi; Akachar, Jihane; Lmimouni, Badreddine; El Harti, Jaouad; Belyamani, Lahcen; Ibrahimi, Azeddine
Abstract: The novel coronavirus, SARS-CoV-2, has infected more than 10 million people and caused more than 502, 539 deaths worldwide as of June 2020. The explosive spread of the virus and the rapid increase in the number of cases require the immediate development of effective therapies and vaccines as well as accurate diagnosis tools. The pathogenesis of the disease is triggered by the entry of SARS-CoV-2 via its spike protein into ACE2-bearing host cells, particularly pneumocytes, resulting in overactivation of the immune system, which attacks the infected cells and damages the lung tissue. The interaction of the SARS-CoV-2 receptor binding domain (RBD) with host cells is primarily mediated by the N-terminal helix of ACE2; thus, inhibition of the spike-ACE2 interaction may be a promising therapeutic strategy for blocking the virus entry into host cells. In this paper, we used an in-silico approach to explore small-molecule α-helix mimetics as inhibitors that may disrupt the attachment of SARS-CoV-2 to ACE2. First, the RBD-ACE2 interface in the 6M0J structure was studied by the MM-GBSA decomposition module of the HawkDock server, which led to the identification of two critical target regions in the RBD. Next, two virtual screening experiments of 7236 α-helix mimetics from ASINEX were conducted on the above regions using the iDock tool, which resulted in 10 candidates with favorable binding affinities. Finally, the stability of RBD complexes with the top-two ranked compounds was further validated by 100 ns of molecular dynamics simulations. Communicated by Ramaswamy H. Sarma